2018
DOI: 10.12669/pjms.346.15722
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of oral antiviral (Sofosbuvir/Ledipasvir) in treating children with HCV infection

Abstract: Objectives:To determine the efficacy of (Sofosbuvir/ledipasvir) in treating children with HCV infection.Methods:This study was conducted at Gastroenterology, Hepatology Center /Pediatrics department and the Central Child Teaching Hospital, Baghdad / Iraq from April 2017 to January 2018. Patients with positive HCV PCR, aged 7 to 18 years were enrolled. History, clinical examinations and investigations were conducted. HCV genotyping was done (if affordable). Sofosbuvir/Ledipasvir was given to all patients once d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In total, 39 references met the inclusion criteria. Twenty‐eight papers were published as full‐text articles 3‐8,11‐32 and 11 as abstracts 33‐43 . Two studies were randomised clinical trials, 27,33 whereas all the other studies were nonrandomised studies.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 39 references met the inclusion criteria. Twenty‐eight papers were published as full‐text articles 3‐8,11‐32 and 11 as abstracts 33‐43 . Two studies were randomised clinical trials, 27,33 whereas all the other studies were nonrandomised studies.…”
Section: Resultsmentioning
confidence: 99%
“…49 In 2017, the U.S. Food and Drug Administration (FDA) and the European Medicines Agency (EMA) approved a fixeddose DAA combination of sofosbuvir and ledipasvir, as well as the combination sofosbuvir plus ribavirin, for the treatment of adolescents (12-17-years old) with chronic hepatitis C. 50 Preliminary results on the use of DAAs in pediatric patients are available for the fixed-dose combination sofosbuvir and ledipasvir in children aged 6 to 17 years for genotype 1 or 4 infection. 51,52 In HCV-infected 12 to 17year-olds who received oral fixed-dose combinations of sofosbuvir and ledipasvir daily for 12 weeks, tests for HCV RNA gave negative results in all patients at weeks 8 and 12 and at SVR12. 53 In these patients, asthenia was the most common adverse effect, followed by headache.…”
Section: Treatment Of Children With Hcv Infectionmentioning
confidence: 99%
“…Similar results were reported in other studies. In study by Alkaaby and Al‐Ethawi, 23 the ratio of males was 66%, and it was 65% in the study by El‐Karaksy et al 19 28 of the 39 patients treated with DAAs (72%) were below 12 years, and they showed good compliance. Similar observation was found in children 6 to <18 years old in other studies , 20,24 which showed that treatment with SOF/LED was well tolerated in this younger population even in children 3 to <6 years old; treatment was well tolerated and highly effective according results showed by Schwarz et al 20 Almost half of our patients (45%) were exposed to more than one risk factor for infection.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, a systematic review and meta‐analysis of 331 Egyptian studies found the most commonly reported risk factors for infection to be mass parenteral anti‐schistosomal treatment campaign exposure, dialysis, transfusion, surgery, frequent injections and dental procedures 25 while vertical transmission is the main route of transmission of HCV infection in the contemporary population of children with chronic infection in Europe 26 . We had 26.7% (16 of 60) of patients with associated comorbidities (Table 2), while 86.36% (20 of 22) of cases enrolled in the study by Alkaaby and Al‐Ethawi 23 had associated comorbidities (thalassaemia, leukaemia and Hodgkin's disease), and 33% (20 of 60) of patients had associated chronic comorbid conditions in the study by Abdullatif et al 27 Before treatment, liver enzymes were elevated in one sixth (16.7%) of our patients (36.4% in group 1, 16.7% in group 2 and 12.8% in group 3) and at the end of treatment normalisation of liver enzymes occurred in all our patients and this is the same in the study by Elsharkawy et al 28 All of our patients still have normal liver enzymes level after SVR 24. However, in the study by El‐Karaksy et al, 19 ALT and AST were elevated in 34 (85%) and 20 patients (50%), respectively, before treatment, and at end of treatment, ALT and AST were normalised in all patients except 5 (two with elevated both ALT and AST, 1 with elevated ALT only and two with elevated AST only).…”
Section: Discussionmentioning
confidence: 99%